2019
DOI: 10.1055/s-0039-3400296
|View full text |Cite
|
Sign up to set email alerts
|

Dural Venous Sinus Thrombosis after Vestibular Schwannoma Surgery: The Anticoagulation Dilemma

Abstract: Introduction Dural venous sinus thrombosis (DVST) is a relatively understudied complication of vestibular schwannoma (VS) surgery. Several studies have examined this topic; however, there is limited data on the incidence, clinical progression, and proper management of this patient population. Methods A retrospective review was performed for patients undergoing surgery for VS at a single institution. All postoperative imaging was reviewed for incidence of DVST. Demographic data were collected includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Our results are consistent with the more recent trend in CPA surgery of performing routine postoperative MRI, which has the highest sensitivity and specificity of diagnostic techniques for detection of cerebral venous thrombi (13). Concordant with other recent studies, dural venous thrombosis among our patients was rarely symptomatic (7,8). Only 1 (3.1%) of 32 patients with CVT was significantly symptomatic after surgery, suggesting that most patients with thrombi would remain undetected without imaging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with the more recent trend in CPA surgery of performing routine postoperative MRI, which has the highest sensitivity and specificity of diagnostic techniques for detection of cerebral venous thrombi (13). Concordant with other recent studies, dural venous thrombosis among our patients was rarely symptomatic (7,8). Only 1 (3.1%) of 32 patients with CVT was significantly symptomatic after surgery, suggesting that most patients with thrombi would remain undetected without imaging.…”
Section: Discussionsupporting
confidence: 93%
“…Thirty-one of our 32 patients with thrombi were followed postoperatively with repeat imaging; 80.6% of these patients experienced resolution of thrombi at a follow-up interval ranging from 5 to 39 months, a rate consistent to the rate noted by Guazzo et al (7), where 11 of 18 patients had resolution of thrombosis by one year. The lower rate of thrombosis resolution (22.7%) reported by Brahimaj et al (8) may be a result of their institutional practice of not routinely obtaining postoperative imaging for vestibular schwannomas, so there is limited ability to directly compare.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Brahimaj et al reported a unusually higher incidence of CVST after vestibular schwannoma surgery compared with other similar series, but they did not observe any symptomatic patient despite none was treated with anticoagulation [4]. According to their evidence, they did not suggest a routinely use of dedicated vascular imaging such as CT or MR venograms with possible time-of-ight sequences to better delineate the presence of a sinus thrombosis.…”
Section: Hints Precautions and Therapeutic Considerationsmentioning
confidence: 90%
“…However, other recent studies have shown that the rate of venous thrombosis after posterior fossa surgery is even greater when reviewed in a retrospective manner [22]. Brahimaj et al, in particular, reported about 35% of CVST incidence after vestibular schwannoma surgery [4]. It remains uncertain the reason why the majority of CVST are not identi ed on initial postoperative imaging.…”
Section: Infratentorial Cvstmentioning
confidence: 99%
“…Finally, anticoagulation is not usually indicated, and few reports have shown safety in close monitoring of these cases. 4–6 …”
Section: Transcriptmentioning
confidence: 99%